The contribution of conservation agriculture in promoting food security among smallholder farmers in ward 15 Zaka district (2008-2014) - Mawire, Delight Martin (Midlands State University, 2017)
Conservation Agriculture (CA) is widely adopted in Zimbabwe, because it is well recognized as a climate adaptation measure. As a matter of fact CA improves yield by 50-100 percent as outlined by Mazvimavi. This research is primarily focusing on assessing the contribution of CA in enhancing household food security of smallholder farmers in ward 15 Zaka district. However qualitative research method is employed in this research and tools used include questionnaire, interviews and field observation among others. Full success of CA in promoting food security in Zimbabwe is threatened by a number of factors which ranges from economic, social, political and environment as shall be explained in chapter 4. Therefore the findings of this study shows that, though there are some notable challenges faced in CA but its benefits remain outstanding as clearly outlined by farmers in chapter 3.